Modeling, description, and characterization of fractal pore via mathematical morphology - Teo, Lay Lian; Sagar, B. S. Daya (2006)
The aim of this paper is to provide description of fast, simple computational algorithms based upon mathematical morphology techniques to extract descriptions of pore channels - throats - and bodies and to represent them in 3D space, and to produce statistical characterization of their descriptions. Towards this goal, a model fractal binary pore is considered and is eroded recursively to generate different slices possessing decreasing degrees of porosity. By employing simple morphology-based approach, each slice of this pore space is decomposed into pore-channel, pore-throat, and pore-body, which are abstract structures that summarize the overall connectivity, orientation, and shape of the pore space. We consider the pore slices and their corresponding morphological quantities to stack them to further represent them in 3D space. We further provide a formulation essentially based on set theory to represent these three morphologic quantities to connect them appropriately across slices. The connected quantities are further fragmented to designate each fragmented portion with orders ranging from 1 to N.